The elements of real analysis - Bartle, Robert G. (Robert Gardner), 1927- (New York : John Wiley and Sons, 1976)
This book is about: A glimpse at set theory; The real numbers; The topology of cartesian spaces; Convergence; Continuous functions; ...
Keywords: Mathematical analysis; Mathematical analysis